Predictions the GDP of Iraq by using Grey –Linear Regression Combined Model - Rahim, Sham Azad; Salih, Shahla Othman; Hamdin, Ayad Othman; Taher, Hindreen Abdullah (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
Gross Domestic Product (GDP) is the total pecuniary or mart value of all final commodity and services that are produced within country's borders in a given time. We choose GDP to predict in Iraq since 2000 to 2018.The state and governments rely on GDP to help shape policy or decide how much public spending is affordable. Combining grey regression is a modern statistical technique of modeling, using this type of model is related to its highly accuracy therefor, in this study we used combined grey regression model to predict the gross domestic production of Iraq because it gives less Mse than grey or regression models alone which is equal to 1.3165 and estimated parameter of grey C1, regression C2 are equals to (2.9 and 0.205) respectively and the intercept C3 is equal to 1.8569 the outcome showed that the new model could attain preferable predicting result contrasted with different predicting methods.